A study of complications and outcome of hypospadias repair at a tertiary care hospital of south Gujarat, India - Nema, Archana A.; Varia, Dilip J. (International Surgery Journal, 2018)
Background: In clinical practice, many factors influence the choice of surgical technique for hypospadias repair. With this background, we evaluated various methods of surgical repairs of hypospadias with their complications and outcomes. Methods: This prospective study was conducted at a tertiary care hospital of South Gujarat, India including 32 patients of hypospadias. All patents were followed after an interval of one week, one month, three months and six months after discharge and complications were recorded. Results: Out of 32, 20 (62%) of patients were having distal hypospadias while 11 (35%) had proximal hypospadias. Eleven patients were operated with TPIF repair and Snodgrass repair each while 4 patients were operated with stage 1 and stage 2 repair each. In TPIF group, 7(60%) patients developed superficial skin necrosis which in Snodgrass group, 5 (45%) patients developed wound infection & oedema. Delayed complications were seen in only 2 cases of surgical repair. Out of 32, 31(96%) patients had satisfactory shape of penis while 1 (4%) patient had sub-optimal cosmetic result. Conclusions: Most common type of hypospadias was distal type in our study. Approximately one third patients were had their hypospadias repaired by TPIF Repair and same percent by Snodgrass Repair. Skin necrosis and wound infection were the most common early complication of the hypospadias repair. Urethral fistula remains the most worrying complication of surgery. TPIF Repair is one of the method which reduces rate of complications.